Compliance with the World Organisation for Animal Health guidelines for poultry production in Grenada. Issue 3 (1st September 2017) - Glasgow, L.; Forde, M.; Fletcher, S.; Keku, E.
Abstract : The tri-island state of Grenada, Carriacou, and Petit Martinique's legislative and institutional compliance with the World Organisation for Animal Health's (OIE) guidelines on antimicrobial utilisation in poultry production is reviewed in this paper. This includes legislative and other institutional documents, coupled with interviews with veterinary officers, health officers and managers of the veterinary drug distribution centres were conducted to evaluate the extent of Grenada's compliance with the OIE's Terrestrial Animal Health Code in the use of antimicrobials in poultry production. Five thematic areas were evaluated: 1) legislative and institutional arrangements; 2) surveillance and reporting; 3) risks associated with the importation of poultry meat products; 4) ante - and post-mortem inspection; and 5) procurement and use of antimicrobials. The information revealed that the current legislative framework in Grenada does not adequately address poultry food safety and that there is a need to strengthen the synergies between the agricultural and health sectors to enable a more thorough monitoring of antimicrobials use in poultry production. There is a need to strengthen epidemiology of zoonotic diseases, provisioning of education and information for key stakeholders about the use of antibiotics and the development of a system to monitor antibiotic procurement, distribution and use in Grenada. These findings have implications for other small island states in the Caribbean that have similar limitations in institutional capacity and knowledge deficits in the prudent use of antibiotics.